Expression of multidrug resistance proteins in retinoblastoma - Shukla, Swati (Int J Ophthalmol, 2017)
AIM: To elucidate the mechanism of multidrug resistance in retinoblastoma, and to acquire more insights into in vivo drug resistance. METHODS: Three anticancer drug resistant Y79 human RB cells were generated against vincristine, etoposide or carboplatin, which are used for conventional chemotherapy in RB. Primary cultures from enucleated eyes after chemotherapy (PCNC) were also prepared. Their chemosensitivity to chemotherapeutic agents (vincristine, etoposide and carboplatin) were measured using MTT assay. Western blot analysis was performed to evaluate the expression of p53, Bcl-2 and various multidrug resistant proteins in retinoblastoma cells. RESULTS: Following exposure to chemotherapeutic drugs, PCNC showed less sensitivity to drugs. No significant changes observed in the p53 expression, whereas Bcl-2 expression was found to be increased in the drug resistant cells as well as in PCNC. Increased expression of P-glycoprotein (P-gp) was observed in drug resistant Y79 cells; however there was no significant change in the expression of P-gp found between primary cultures of primarily enucleated eyes and PCNC. Multidrug resistance protein 1 (Mrp-1) expression was found to be elevated in the drug resistant Y79 cells as well as in PCNC. No significant change in the expression of lung resistance associated protein (Lrp) was observed in the drug resistant Y79 cells as well as in PCNC. CONCLUSION: Our results suggest that multidrug resistant proteins are intrinsically present in retinoblastoma which causes treatment failure in managing retinoblastoma with chemotherapy.